Social Media Usage and Brand Image on Product Purchasing Decision (Survey at @etawalinmart) - Girsang, Lasmery RM; Situmeang, llona V.O (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The marketers are looking at TikTok as a promising marketing platform to boost brand awareness and product sales. Applying TikTok media, user can practically make purchases and orders for various products, without having to go through a complicated process. Nowadays, the existence of TikTok platform become a popular marketing platform, makes it easy for consumers to access information about the products. Also, relating to the object of this article, through TikTok platform, consumers easily get complete information about Etawa Milk products, from prices, distributors, benefits and ongoing promotions. Hence, this platform is the right media to reach consumers. This research is conducted to verify the influence between all variables, namely: Social Media Usage, Brand Image and Purchasing Decision. By applying quantitative research, this article uses explanative-survey method to 100 followers of @etawalinmart. As the results, there are influences among all variables. As the conclusion, for all variables, it is stated that there are significant simultaneous influences between the Usage of TikTok media and Brand Image on Purchasing Decisions with the results of the F Test obtaining a value of <,001 (Sig) < 0.05 (ð›¼) or 79,345 (F count) > 3.09 (F table). Finally, the implication of this article will encourage other researches concerning with the power of media through Technological Determinism Theory towards other digital platforms.